2018
DOI: 10.1080/17461391.2018.1541256
|View full text |Cite
|
Sign up to set email alerts
|

Running speed‐induced changes in foot contact pattern influence impact loading rate

Abstract: Purpose. We aimed to determine the effect of speed-induced changes in foot contact patterns on the vertical instantaneous loading rate (VILR). We hypothesized that transition runners, i.e. runners that shift towards a mid-(MF) or forefoot contact pattern (FF) when running speed increases, show smaller increases in VILR than non-transition runners, i.e. runners that remain with a rearfoot contact pattern (RF). Methods. Fifty-two male and female runners ran overground at 3.2, 4.1, 5.1 and 6.2 m s −1 . Ground rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Moreover, Larson et al (2011) observed an increase in the RFS prevalence from 88% to 93% between the 10 km and 32 km marks of the 2009 Manchester City Marathon (New Hampshire, USA) in a mostly North American cohort of runners. Although the medical implications of alterations in footstrike patterns in-race are yet to be fully elucidated; footstrike pattern change suggests neuromuscular fatigue (Jewell et al, 2017), slower running speeds (Breine et al, 2019;Cheung et al, 2017), and overall lower running performance (Bovalino et al, 2020;Latorre-Rom an et al, 2015). To our knowledge, no study has yet to report alterations in self-selected footstrike patterns in Asian recreational runners during a marathon, which would suggest racing-induced fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Larson et al (2011) observed an increase in the RFS prevalence from 88% to 93% between the 10 km and 32 km marks of the 2009 Manchester City Marathon (New Hampshire, USA) in a mostly North American cohort of runners. Although the medical implications of alterations in footstrike patterns in-race are yet to be fully elucidated; footstrike pattern change suggests neuromuscular fatigue (Jewell et al, 2017), slower running speeds (Breine et al, 2019;Cheung et al, 2017), and overall lower running performance (Bovalino et al, 2020;Latorre-Rom an et al, 2015). To our knowledge, no study has yet to report alterations in self-selected footstrike patterns in Asian recreational runners during a marathon, which would suggest racing-induced fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Running GRF is related to impact shock, loading accumulation, and even stress syndrome in the lower extremity (Lieberman et al, 2010;Breine et al, 2019). While comparing the VALRs in the males and females across the four speeds, significance was observed only during 2.7 m/s without significance in other speeds.…”
Section: Discussionmentioning
confidence: 93%
“…On the contrary, the second peak (push-off) force (PC1) and LR (PC2) took over the transient (PC3) and first peak (PC4) in male runners. Evidence was that females and males might respond differently as running speed incrementing (Breine et al, 2019;Clermont et al, 2019). In specifics, the females showed variations in the impact absorption and force output, whereas males changed the timing of force output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stance time in mid/forefoot strike is shorter. Faster some people run, more typical such strike patterns are, 51,52 suggesting subgroups, that is, some runners change, while others do not, their foot strike pattern when they run faster. Besides, barefoot running might provide more sensory information during foot strike.…”
Section: Referencesmentioning
confidence: 99%